COULD THE DEATH OF A BC OR NURSE HAVE BEEN PREVENTED BY USING THE HANDS-FREE TECHNIQUE? - Haines, Ted; Stringer, Bernadette (Operating Room Nurses Association of Canada Journal, 2007)
In 1991, Bernadette Stringer, a long time BC Nurses’ Union health and safety representative, learned about the death of a 48 year old Victoria, B.C., OR nurse who had sustained a hepatitis C contaminated needlestick. This incident led to a study evaluating the hands-free technique’s ability to decrease the risk of percutaneous injury, glove tear and mucocutaneous contamination during surgery that Ms. Stringer carried out in partial fulfillment of her Ph.D. (granted in 1998, by McGill University’s Joint Departments of Epidemiology, Biostatistics and Occupational Health, in the Faculty ofMedicine). That study’s main findings were published in 2002 in one of the British Medical Journal’s publications, Occupational and Environmental Medicine 2. The following article will discuss aspects of Bev Holmwood’s case, review the literature on the hands-free technique, and describe a new study that has again evaluated the hands-free technique’s effectiveness.